(3eaGgje GJUGdjI (B:s (3ebGQHI LjfjGdhLjI aj GTcGdjGJ GdJCUjd h TQhW GdJhWjf (B/s - (3LaGadI, OGhOs ((3GdLRGFQ (B:s (3OGQ jhJhHjG ddfTQ h GdJhRjY ,s, 2022)
(3Gf ehVhY gPG GdYed gh Mbd Ydhe GdGYdGe h GdGJUGd h GdPj jSYi dCf jhVM HYV GdeaGgje GdCSGSjI GdJj JMce gPG GdJNUU cYjfI abW eY GdJCcjO Ydi GdMGLI Edi GdbjGe HfaS GdTF eY eaGgje CNQi dG Jbd CgejI h JJdNU acQI GdJhVjM gPg aj eMGhdI JCUjd GdeaGgje GdeSJNOeI ef bHd GdHGMKjjf h GdJj YGOI eG JJe JQLeJgG NGQL GdSjGb eeG jNQLgG Yf eYfGgG GdCUdj Ydi CSGS Cf gPG GdMbd gh JNUU ZQHj HGeJjGR h HGdJGdj hLH Cf jJe JfGhd GdeUWdMGJ GdeJYdbI Hg habG ddCeGfI GdYdejI GdJj JJWdH GdUQGeI h GdMRe aj YedjI JhWjfgG YQHjG h dPdc aEf gPG GdYed jMGhd GdaUd Hjf GSJNOGeGJ eJYOOI deUWdMGJ eJaQbI JWdb Ydi faS GdcjGfGJ GddZhjI eKd GdGJUGd h GdJhGUd GdTHcGJ GdGLJeGYjI GdQbejI h ehGbY GdJhGUd GdGLJeGYj GdGYdGe GdMchej h GYdGe GdNOeI GdYehejI Gf GdgOa ef gPG GdYed gheMGhdI JCUjd HYV GdGSJNOGeGJ GddZhjI deaGgje ZQHjI h GdYed Ydi JhWjfgG aj GdHMK GdYdej GdYQHj habG dCNdGbjGJ GdJQLeI GdYdejI GdeJYdbI HGdhaGA HGdeYfi h GdOdGdI h Pdc aj SHjd GHJcGQ eSYi jYed Ydi GdJCSjS dJhWjf GdeYQaI GdZQHjI aj GfJXGQ GWdGb YedjI GfJGL GdeYQaI aj GdhWf GdYQHj GdJj dG jecf Gf JJMbb GdG HGdbVGA Ydi GSHGH GdJNda GdePchQI SGHbG(B.s
Keywords: (3GTcGdjGJ GdJCUjds; (3GdGJUGds; (3LjfjGdhLjIs